2020
DOI: 10.1108/jkm-02-2020-0127
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge-oriented leadership, knowledge management behaviour and innovation performance in project-based SMEs. The moderating role of goal orientations

Abstract: Purpose This study aims to examine the association of knowledge-oriented leadership (KOL), knowledge management (KM) behaviour and innovation performance in project-based small and medium-sized enterprises. It investigates the moderation of goal-orientation in the relationship of KOL with knowledge-acquisition, transfer, documentation and application. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
95
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 65 publications
9
95
0
3
Order By: Relevance
“…A significant research stream explored the role of knowledge and the development of routines (Carayannis et al , 2017) and capabilities (Bingham et al , 2019; Eggers and Kaplan, 2013). Meanwhile, the understanding of the strategic notion of knowledge and KM for business performance can be considered a turning point in the field of research (Paoloni et al , 2020; Ensslin et al , 2020; Zia, 2020; Pellegrini et al , 2020; Obeso et al , 2020; Heisig et al , 2016; Nag and Gioia, 2012). Recently, scholars (Zhang et al , 2020; Loon, 2019) have defined KM as a comprehensive three-set of strategies, processes and practices concerning knowledge generation, dissemination and application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A significant research stream explored the role of knowledge and the development of routines (Carayannis et al , 2017) and capabilities (Bingham et al , 2019; Eggers and Kaplan, 2013). Meanwhile, the understanding of the strategic notion of knowledge and KM for business performance can be considered a turning point in the field of research (Paoloni et al , 2020; Ensslin et al , 2020; Zia, 2020; Pellegrini et al , 2020; Obeso et al , 2020; Heisig et al , 2016; Nag and Gioia, 2012). Recently, scholars (Zhang et al , 2020; Loon, 2019) have defined KM as a comprehensive three-set of strategies, processes and practices concerning knowledge generation, dissemination and application.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stanislas [ 59 ] analyzed the indicators that affect sustainable construction and found that the personal charm of the project manager is one of the crucial indicators that can improve leadership effectiveness. Zia [ 60 ] reckoned that the emotional intelligence of project managers could improve partnerships and promote effective communication between project members. Maqbool [ 61 ] pointed out project managers with high emotional intelligence who bear the desired competencies and exhibit transformational leadership behavior are influential leaders and ensure higher success in projects than their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…One of these resources/capabilities is knowledge, and the ability to manage it (i.e., the knowledge management capability) has been continuously linked to business innovation performance (Zia 2020 ). Firms with ICT capabilities can adequately capture and manage information about the market and their customers, enabling them to develop appropriate innovation processes to satisfy their customers.…”
Section: Hypotheses Developmentmentioning
confidence: 99%